Dynamic electrophysical characterization of porous silicon humidity sensing - Bravina, S.; Morozovsky, N.; Boukroub, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The results of the investigation of changes of parameters of bipolar and unipolar dynamic current-voltage characteristics and transient currents as well as dynamic bipolar charge-voltage loops connected with the pulse change of humidity for the samples of por-Si are presented. The hysteresis view of charge-voltage and current-voltage curves is characteristic for poling processes in the space charge region similar to that observed in the case of typical ionic conductors. Observed phases of transformation of investigated electrophysical characteristics reflect the time sсale of processes in the consequence “adsorption – dissociation and transfer – desorption”. The efficiency of using the methods of dynamic electrophysical characterization for studying characteristics of porous materials under fast humidity changes was demonstrated.